Logics of Legitimacy : Three Traditions of Public Administration Praxis. - Stout, Margaret (Public administration and public policy., 2012)
WHY AND HOW THE TRADITIONS FRAMEWORK WAS CREATEDThe Legitimacy QuestionWhy Worry about Role Conceptualization? Professional Socialization in Public AdministrationIntroductionThe Importance of Role Conceptualization in Public AdministrationWhat Is Role Conceptualization?How Role Conception Is Formed Step 1: Practitioner Acts as Role Taker Step 2: Role Performance Is Performed and Assessed Step 3: Experience Impacts Role Conception and Conceptualization Step 4: Pedagogy Transmits Role ConceptualizationsUsing Theoretical Frameworks as Interpretive LensesIntroductionDeveloping and.